Tecendo Vidas: Cultura e Trabalho das Rendeiras da Prainha de Aquiraz-CE - Drumond, Terezinha Bandeira Pimentel (2006)
The present dissertation analyses the construction, in 1979, of the “Centro das Rendeiras da Prainha” (community located at Aquiraz, Ceará, Brazil), and emphasizes this fact as a landmark of the local craftwomen’s organization and professionalization. Focusing on oral techniques, added to the investigation of some institutional documentation of the “Associação das Rendeiras da Prainha”, this research aimed to highlight traditional cultures (such as “renda de bilros” and fishing) as complementary activities to local families’ survival and maintenance. Finally, this study evidences the rendeiras’ political action in the perspective of associative culture, as well as their practices in the creation and maintenance of their place of work; something that is possible once considering the limitation of the object of study, through historiographic production dedicated to the social history of labour.